A Calculating Actual Stature of Elderly through Arm Span and Knee Height Measurements - Pertiwi, Julia; Kartasurya, Martha Irene; Lukmono, Djoko Tri Hadi; Setyawan, Henry; Martini, Martini (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Background: Most of estimation height study was calculated with one predictor. This research tried to arrange regression model by combining two predictors. Methods: The type of study was observational with cross sectional design. The study population is aged 60-69 years old in Wonogiri District. The sample size of 136 included 65 men and 71 women with purposive sampling technique. Data collection technique is observation on anthropometry measurement. Data analyzed with Pearson Product Moment, Unpaired T-test and Linear Regression. Results: Arm span is positively correlated with value of p<0.001; r=0.886 in men and p<0.001; r=0.992 in women. Knee height is positively correlated with p value <0.001; r=0.989 in men and p<0.001; r=0.986 in women. The height estimated from the arm spanâknee height formulas: Women height (cm) = 40.915+[0.457 x AS (cm)]+[0.818 x KH (cm)]. Men height (cm) = 34.426+[0.513 x AS (cm)]+[0.813 x KH (cm)]. The highest overestimation happen at Chumleaâs formula in men at women group (6.01 cm) and highest underestimation happen at Fatmahâs formula in women group (-0.72 cm). Conclusions: Arm span is more accurately used in women, whereas knee height is more accurate in men. Predictor combinations can be used to predict height more accurately.